Analisis Tanggung Jawab Negara Dalam Pemberian Bantuan Hukum Kepada Masyarakat Tidak Mampu Berdasarkan Undang-Undang Nomor 16 Tahun 2011 Tentang Bantuan Hukum - Ramadhan, Irvan; Putra, Firmansyah (Limbago: Journal of Constitutional Law, 2024)
Abstract This research aims to determine the state's responsibility in providing legal aid. The approach method used in this research is normative juridical which is descriptive in nature. The data source is secondary data in the form of applicable laws and regulations. Data collection techniques using literature study. The data analysis method uses the analytical method. The research results show that the juridical basis for implementing the provision of non-litigation legal assistance is based on: (1) Law of the Republic of Indonesia No. 16 of 2011 concerning free legal aid to recipients of legal aid which include poor people or groups of people who are facing legal problems, (2) Law of the Republic of Indonesia no. 48 of 2009 concerning Judicial Power, (3) Law of the Republic of Indonesia No. 49 of 2009 concerning General Courts, (4) Law of the Republic of Indonesia No. 50 of 2009 concerning the Second Amendment to Law no. 7 of 1989 concerning Religious Courts, (5) Republic of Indonesia Law no. 51 of 2009 concerning State Administrative Courts, (6) Law of the Republic of Indonesia no. 18 of 2003 concerning Advocates, and (7) Republic of Indonesia Law no. 8 of 1981 concerning the Criminal Procedure Code. Furthermore, the obstacles faced in assisting in the resolution of non-litigation cases include: (1) The public's lack of knowledge about the legal problems that befall them, (2) Insufficient human resources, and (3) Insufficient financing budget. Keywords:legal aid institutions, poor communities Abstrak Penelitian ini bertujuan untuk mengetahui tanggung jawab negara dalam pemberian bantuan hukum. Metode pendekatan yang digunakan dalam penelitian ini adalah metode pendekatan yuridis normatif yang bersifat deskriptif. Sumber data merupakan data sekunder berupa peraturan perundang-undangan yang berlaku. Teknik pengumpulan data dengan studi kepustakaan. Metode analisis data menggunakan metode analisis. Hasil penelitian ini menunjukkan bahwa pelaksanaan pemberian bantuan hukum bagi masyarakat tidak mampu yang diatur dalam Undang-Undang No. 16 Tahun 2011 tentang bantuan hukum telah berjalan sesuai dengan aturan yang berlaku. Serta syarat yang dijadikan pertimbangan dalam pemberian bantuan hukum bagi masyarakat tidak mampu yakni Mengajukan permohonan secara tertulis yang berisi sekurang-kurangnya identitas pemohon dan uraian singkat mengenai pokok persoalan yang dimohonkan bantuan hukum, Menyerahkan dokumen yang berkenaan dengan perkara, Melampirkan surat keterangan miskin dari lurah, kepala desa, atau pejabat yang setingkat di tempat tinggal pemohon bantuan hukum. Kata kunci: lembaga bantuan hukum, masyarakat miskin